Learning Speaking Skills at The Foreign Language Development Institution Of Manbaul Hikam Sidoarjo Indonesia - Alfatawi, Ahmad Talkhis; Nu’man, Mohammad (Journal of Arabic Language Studies and Teaching, 2024)
This study aims to determine the implementation of the question-and-answer method in teaching speaking skills to students at the Manbaul Hikam Putat Tanggulangin Sidoarjo Islamic Boarding School and to find out the supporting and inhibiting factors. This study uses a qualitative research method with a type of field research. The data collection techniques are through observation, interviews and documentation. At the same time, the data analysis technique uses descriptive analysis techniques. From the results of the study, it can be concluded that: 1) The steps of learning using the question and answer method consist of initial activities, core activities and closing activities. 2) Supporting factors: Teachers master textbooks and learning methods well, there is a special dormitory for some students, and there is a language environment. Inhibiting factors: Teaching early grades requires extra effort because the teacher minimizes the use of the source language or mother tongue when speaking or explaining material to students.